Mariama Bâ and the Politics of the Family - Laurie Edson (Studies in 20th & 21st Century Literature, 1993)
The Senegalese woman writer, Mariama Bâ, chronicles a changing society in post colonial Senegal, caught between the attraction of modernization and the resistance of traditional beliefs. Her award-winning novel, Une si longue lettre, is examined as an example of the kind of subversive "journalism-vérité" proposed by Paulin Hountondji: an anecdotal reconstruction of facts combined with organization and interpretation that leads readers to an awareness of the real conditions of daily life and exposes the structures that make them possible. Bâ's novel exemplifies this "return to the real" not only because Bâ speaks about and exposes the all-too-common reality of abandonment in the details of everyday reality. This essay reads the novel against the background of social, cultural, and political events in Senegal in the 1970s, including the passage of the Family Code into law and the resurgence of Islamic fundamentalism. It addresses the modern perversion of the system of polygamy and the economic and social ramifications of abandonment for women, children, and the country. It also addresses issues of class, caste prejudices, education, forced marriage, and the figure of the progressive mother.
Keywords: Mariama Bâ; Senegalese; woman writer; Senegalese woman writer; changing society; colonial Senegal; post colonial Senegal; modernization; traditional beliefs; resistance; Une si longue lettre; journalism-vérité; subversive; Paulin Hountondjireal; daily life; structures; return to the real; abandonment; social; cultural; political; Senegal in the 1970s; 1970s; Family Code into law; Family Code; Islamic fundamentalism; Islam; polygamy; economic; ramifications; women; children; country; class; caste prejudices; education; forced marriage; progressive mother